Karyopherin alpha2 is essential for rRNA transcription and protein synthesis in proliferative keratinocytes. - Noriko Umegaki-Arao (PLoS ONE, 2013)
Karyopherin proteins mediate nucleocytoplasmic trafficking and are critical for protein and RNA subcellular localization. Recent studies suggest KPNA2 expression is induced in tumor cells and is strongly associated with prognosis, although the precise roles and mechanisms of KPNA2 overexpression in proliferative disorders have not been defined. We found that KPNA2 expression is induced in various proliferative disorders of the skin such as psoriasis, Bowen's disease, actinic keratosis, squamous cell carcinoma, Paget's disease, Merkel cell carcinoma, and mycosis fungoides. siRNA-mediated KPNA suppression revealed that KPNA2 is essential for significant suppression of HaCaT proliferation under starvation conditions. Ribosomal RNA transcription and protein synthesis were suppressed by starvation combined with knockdown of KPNA (including KPNA2) expression. KPNA2 localized to the nucleolus and interacted with proteins associated with mRNA processing, ribonucleoprotein complex biogenesis, chromatin modification, and transcription, as demonstrated by tandem affinity purification and mass spectrometry. KPNA2 may be an important promoter of ribosomal RNA and protein synthesis in tumor cells.